2004
DOI: 10.1007/s00244-004-3027-z
|View full text |Cite
|
Sign up to set email alerts
|

Lead in Feathers and ?-Aminolevulinic Acid Dehydratase Activity in Three Raptor Species from an Unpolluted Mediterranean Forest (Southeastern Spain)

Abstract: This paper presents the levels of lead found in the feathers of adult and blood of nestlings of booted eagle (Hieraaetus pennatus), European buzzard ( Buteo buteo), and goshawk (Accipiter gentilis) sampled in the 1999 and 2000 breeding seasons in a Mediterranean forest of the Province of Murcia (Southeastern Spain) located far from potential sources of metal contamination. Levels of delta-aminolevulinic acid dehydratase activity (delta-ALAD) in blood were also measured in the nestlings. Lead concentrations ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 1 publication
3
23
0
Order By: Relevance
“…Mean concentration of blood lead levels for the whole population (3.73 ± 4.2 lg/dl) is close to the range considered by several authors for birds non-exposed to lead (García-Fernández et al 1997;Henny et al 1991;Martínez-López et al 2004;Scheuhammer, 1989) and, therefore, similar to the levels found in several raptor species inhabiting non-polluted areas (Henny et al 1994;Martínez-López et al 2004;McBride et al 2004), or even lower if adults were included in other studies (García-Fernández et al 1997) (Table 1). However, about 10% of the samples presented blood lead levels above 10 lg/dl, being in eight individuals higher than 14.87 lg/dl.…”
Section: Blood Lead Levelssupporting
confidence: 64%
“…Mean concentration of blood lead levels for the whole population (3.73 ± 4.2 lg/dl) is close to the range considered by several authors for birds non-exposed to lead (García-Fernández et al 1997;Henny et al 1991;Martínez-López et al 2004;Scheuhammer, 1989) and, therefore, similar to the levels found in several raptor species inhabiting non-polluted areas (Henny et al 1994;Martínez-López et al 2004;McBride et al 2004), or even lower if adults were included in other studies (García-Fernández et al 1997) (Table 1). However, about 10% of the samples presented blood lead levels above 10 lg/dl, being in eight individuals higher than 14.87 lg/dl.…”
Section: Blood Lead Levelssupporting
confidence: 64%
“…(Figures 1 and 2). Finally, other studies have reported feather lead levels as a biomarker of exposure and toxicity (e.g., 34,[50][51][52][53], though to our knowledge none have used serial sampling and stable isotopic analyses to determine the bird's lead exposure history.…”
Section: Resultsmentioning
confidence: 99%
“…We are unaware of any other studies reporting lead in feathers of Golden Eagles. However, Martinez-Lopez et al (2004) reported mean lead level of 0.72 ppm in Booted Eagle (Hieraaetus pennatus) feathers from what they considered an unpolluted environment in Spain. That level is above mean lead feather concentration of Golden Eagles reported here and suggests summer environments of Montana Golden Eagles may be relatively clean.…”
Section: Leadmentioning
confidence: 99%